An unusual complication during anticoagulant therapy - M. T. Vatutin; Y. I. Yakovets; V. B. Kostogryz; N. A. Glynska; D. V. Bort; Y. V. Yeshchenko; Y. P. Gritsenko (Архивъ внутренней медицины, 2015)
The article presents a case report of hematoma after a mosquito bite in the lower part of the lateral periorbital area in a patient receiving warfarin.